A Critical Examination of the Absence of Intent in Establishing Criminal Liability in the Central Jakarta District Court Decision No. 12/Pid.Sus-TPK/2024/PN.Jkt.Pst - Darmawan, Benedictus Ardy (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
This study conducts a critical analysis of Court Decision No. 12/Pid.Sus-TPK/2024/PN.Jkt.Pst, which is deemed to create confusion regarding the role of mens rea (malicious intent) in criminal liability for corruption. Using a normative juridical method and a case study approach, this research examines the case of Karen Agustiawan, the former CEO of Pertamina, who was convicted in an LNG procurement case. The main findings indicate that the Defendant was proven to have no malicious intent to cause state financial loss and did not gain personal profit. Furthermore, the state losses that occurred were attributed more to external factors, such as force majeure and global market changes. The verdict is criticized for disregarding fundamental principles of criminal law, namely actus non facit reum nisi mens sit rea (an act does not make one guilty unless the intent is guilty) and geen straf zonder schuld (no punishment without fault). In conclusion, this research emphasizes that mens rea is a fundamental requirement, and therefore, the absence of malicious intent on the Defendant’s part should have been a central consideration in the judgment.